The mediating role of life satisfaction in the relationship between depression, anxiety, stress and burnout among Portuguese nurses during COVID-19 pandemic - Vera Martins; Carla Serrão; Andreia Teixeira; Luísa Castro; Ivone Duarte (BMC, 2022)
Abstract Background The COVID-19 pandemic had a large consequence on healthcare systems, increasing the risks of psychological issues in health professionals. Nurses, in particular, have been exposed to multiple psychosocial stressors and struggled with intensive work, insufficiency of resources and uncertainty in the face of an unknown disease. Life satisfaction might protect nurses from the consequences of chronic stress. The aim of this study was to explore the mediating role of satisfaction with life in the relationship between depression, stress, anxiety and burnout (personal, work-related, and client-related). Methods A cross-sectional, descriptive, correlational study design was performed, using an online questionnaire distributed via social networks. A total of 379 nurses completed the survey, comprising standardized measures of satisfaction with life, resilience (Resilience Scale), depression, anxiety, stress (Depression Anxiety Stress Scales), and burnout (Copenhagen Burnout Inventory Scale). A hierarchical regression model was estimated for each burnout dimension. Results Participants showed high levels of work, personal and client-related burnout, 57.3%, 57%, and 35.1%, respectively. More than 70% of the respondents had a normal level of depressive symptoms, 66.8% presented normal level of anxiety and 33.5% of the respondents reported mild, moderate, severe or extremely severe symptoms of stress. The results revealed that life satisfaction partially mediated the association between stress and personal burnout, depression and work-related burnout, and the association between anxiety and client-related burnout in nurses. Conclusions The COVID-19 pandemic brought added difficulties for nurses' work conditions, whereby it became necessary to develop adaptative measures that reduce stressors in work environment and promote nurses' life satisfaction.